Arabidopsis retrotransposon virus-like particles and their regulation by epigenetically activated small RNA - Lee, Seung Cho; Ernst, Evan; Berube, Benjamin; Borges, Filipe; Parent, Jean-Sebastien; Ledon, Paul; Schorn, Andrea; Martienssen, Robert A. (Genome Research, 2020)
In Arabidopsis, LTR retrotransposons are activated by mutations in the chromatin gene DECREASE in DNA METHYLATION 1 (DDM1), giving rise to 21- to 22-nt epigenetically activated siRNA (easiRNA) that depend on RNA DEPENDENT RNA POLYMERASE 6 (RDR6). We purified virus-like particles (VLPs) from ddm1 and ddm1rdr6 mutants in which genomic RNA is reverse transcribed into complementary DNA. High-throughput short-read and long-read sequencing of VLP DNA (VLP DNA-seq) revealed a comprehensive catalog of active LTR retrotransposons without the need for mapping transposition, as well as independent of genomic copy number. Linear replication intermediates of the functionally intact COPIA element EVADE revealed multiple central polypurine tracts (cPPTs), a feature shared with HIV in which cPPTs promote nuclear localization. For one member of the ATCOPIA52 subfamily (SISYPHUS), cPPT intermediates were not observed, but abundant circular DNA indicated transposon “suicide” by auto-integration within the VLP. easiRNA targeted EVADE genomic RNA, polysome association of GYPSY (ATHILA) subgenomic RNA, and transcription via histone H3 lysine-9 dimethylation. VLP DNA-seq provides a comprehensive landscape of LTR retrotransposons and their control at transcriptional, post-transcriptional, and reverse transcriptional levels.